MERUBAH KARAKTER BIROKRASI INDONESIA BERDASARKAN UNDANG-UNDANG APARATUR SIPIL NEGARA - Eljawati Eljawati (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Lawin the discussion of this article is the formal state law and the meaning of power is the power of government (government authority). Embody ideas, values,goals become a matter of law that requiredafactual power or driving force or power required. What is meant by such a power is the power tocarryout the function of the law. Law without power will stay as adesires or mereide as that will nevermaterialize.Legaland in deed must, and absolute powert o complement each other, but the law could beleftt idalahridden by power or political power. Thus it is possible the conﬂ ict between law and power.Sioituasiconﬂ ict is the greatest power in its purest form, he could notaccept the restrictions, laws moreover make it work or providere strictions.Law and power relations can also be done through the use of the or etical approach hes PhilllpePhilippe Nonet and Selznickon the relations hip between law and politics. In the context of this paper theauth or wants togive the same meaning between politic sand power, there fore, is nothing but politicalpower. Relevance between law and politic scan bead opted from the description Nonet and Selz nickrelate to the classiﬁ cation of the type of existing law.Kaywords: politic, character and birocratic